Life and work of Cuban and foreign scientists and their contributions to biology - Armiñana-García, Rafael (2025)
The analysis of the qualities of the men of science allows the work in the education in values of the students, it is for this reason that the research that was carried out in fact, aims to propose a compendium, in digital format that contributes to the knowledge of the life and work of the men of science who have made famous discoveries in the field of Biology, for the 7th grade students and teachers of the Basic Urban Secondary School (ESBU) “Javier Calvo Formoso”. For the development of the research, methods of information gathering and processing were used, which allowed to verify the deficiencies related to the life and work of Cuban and foreign scientists, who have made contributions to Biology. In the elaboration of this type of teaching means, for the teaching-learning process in Biology I. The population consisted of 117 students of the ESBU “Javier Calvo Formoso”, who make up the 7th grade enrollment and 4 teachers, but the interview could be carried out with 98 students, which constituted the selected sample, due to the fact that on the days when the instrument was applied in different cases, some students did not attend classes for dissimilar reasons. The illustrations were made to correspond to the pedagogical and hygienic requirements, and comply with the didactic functions and principles for this type of resource. As a result of the research work, the compendium who discovered who?